The Role of Religious Leaders in Curbing the spread of HIV/Aids in Nigeria - Oluduro, Olubayo (Potchefstroom Electronic Law Journal, 2017)
The tragic impact of the HIV/AIDS pandemic in Nigeria and its rate of escalation despite increasing access to health services have been alarming and terrifying. Nigerian people are very religious, yet the impact of the pandemic leaves nothing untouched. The article examines the response of the Nigerian religious leaders to the challenges of the HIV/AIDS pandemic. It discusses some of the challenges facing religious leaders as they grapple with the consequences of this pandemic and explores ways in which they can make a real difference in halting its spread.